Cell proliferation and cytoarchitectural remodeling during spinal cord reconnection in the fresh-water turtle Trachemys dorbignyi - Rehermann, María Inés (2011)
In fresh-water turtles, the bridge connecting the proximal and caudal stumps of transected spinal cords consists of regenerating axons running through a glial cellular matrix. To understand the process leading to the generation of the scaffold bridging the lesion, we analyzed the mitotic activity triggered by spinal injury in animals maintained alive for 20–30 days after spinal cord transection. Flow cytometry and bromodeoxyuridine (BrdU)-labeling experiments revealed a significant increment of cycling cells around the lesion epicenter. BrdU-tagged cells maintained a close association with regenerating axons. Most dividing cells expressed the brain lipid-binding protein (BLBP). Cells with BrdU-positive nuclei expressed glial fibrillary acidic protein. As spinal cord regeneration involves dynamic cell rearrangements, we explored the ultra-structure of the bridge and found cells with the aspect of immature oligodendrocytes forming an embryonic-like microenvironment. These cells supported and ensheathed regenerating axons that were recognized by immunocytological and electron-microscopical procedures. Since functional recovery depends on proper impulse transmission, we examined the anatomical axon-glia relationships near the lesion epicenter. Computer-assisted three-dimensional models revealed helical axon-glial junctions in which the intercellular space appeared to be reduced (5–7 nm). Serial-sectioning analysis revealed that fibril-containing processes provided myelinating axon sheaths. Thus, disruption of the ependymal layer elicits mitotic activity predominantly in radial glia expressing BLBP on the lateral aspects of the ependyma. These cycling cells seem to migrate and contribute to the bridge providing the main support and sheaths for regenerating axons.